Deciphering the mechanism of women’s mental health: a perspective of urban–rural differences - Chen, Changqin; Chen, Ruying; Wang, Qianhui; Zhang, Mengdi; Song, Jinhui; Zuo, Wen; Wu, Rong (Frontiers in Public Health, 2025)
BackgroundMental health accounts for a significant proportion of holistic health and affects women more significantly than men. Livelihood capital, defined as an indicator of these sources available for individuals or households to survive and develop, is a cost-effective field for ameliorating women’s mental health. However, the impact of these multiple factors of livelihood capital on mental health still requires further research Therefore, this study evaluates women’s mental health and investigates the correlation between livelihood capital (including human capital, physical capital, social capital, and financial capital) and women’s mental health.MethodsBased on the 2018 China Labor-force Dynamics Survey, this study explores the relationship and pathways between livelihood capital and women’s mental health, with the structural equation model. It also aimed to examine the impact of relative deprivation under the influence of livelihood capital on women’s mental health, focusing on urban–rural differences.ResultsThe results of this study are as follows: (1) Human capital, social capital and physical capital were positively correlated with women’s mental health, while financial capital showed a negative correlation; (2) Relative deprivation mediates the impact of livelihood capital on women’s mental health; (3) The impact of livelihood capital on women’s mental health is different between urban and rural regions. Urban women were more likely to be influenced by financial capital, whereas human capital, social capital and physical capital were key factors affecting rural women’s mental health. (4) Relative deprivation mediates the impact of livelihood capital on mental health in the rural sample, but not in the urban sample.DiscussionThis study shows a complex relationship among livelihood capital, relative deprivation, and women’s mental health, with notable urban—rural differences. In rural areas, human, social, and physical capital positively affect women’s mental well—being. For example, better education reduces relative deprivation. Social support and improved housing also help. Conversely, financial capital has a negative link with mental health, more so in urban areas, likely due to urban pressure and the wealth—mental health relationship. Based on the findings, several actions are warranted. In social welfare, allocate more resources to rural areas for stronger women’s livelihood capital. Public services should improve rural housing and community integration. Expand and enhance mental health education for rural women. These steps can ease rural women’s mental health challenges and promote fairness in mental health outcomes.